2016
DOI: 10.1177/0042098016631918
|View full text |Cite
|
Sign up to set email alerts
|

Urbanisation, natural amenities and subjective well-being: Evidence from US counties

Abstract: This paper examines the relationships between county-level urbanisation, natural amenities and subjective well-being (SWB) in the US. SWB is measured using individual-level data from the Behavioral Risk Factor Surveillance System (BRFSS) which asks respondents to rate their overall life satisfaction. Using individual-level SWB data allows us to control for several important individual characteristics. The results suggest that urbanisation lowers SWB, with relatively large negative coefficients for residents in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 62 publications
4
47
0
Order By: Relevance
“…Cheshire and Magrini [6] studied population growth in European cities and found that cities with better weather than the country average have grown faster between 1980 and 2000. Winters and Li [7] studied the role of natural amenities for life satisfaction in the US and found that warmer winters have indeed a positive effect on self-reported well-being. These studies highlight that climatic conditions matter for spatial population dynamics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cheshire and Magrini [6] studied population growth in European cities and found that cities with better weather than the country average have grown faster between 1980 and 2000. Winters and Li [7] studied the role of natural amenities for life satisfaction in the US and found that warmer winters have indeed a positive effect on self-reported well-being. These studies highlight that climatic conditions matter for spatial population dynamics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…12 Winters and Li (2017) showed the adverse effects of county population density on life satisfaction. Farmers' ratio was also found to rooted in the Japanese value for interdependence (Uchida et al, 2019); this might be related to the sense of assurance within the Japanese social system and the social norms that are based on mutual trust within this community.…”
Section: Analysesmentioning
confidence: 99%
“…The largest cities get larger, and green space coverage in cities declines as human population density and urbanization increase [1,2]. Growing evidence shows that urbanization decreases perceived well-being [3] and happiness [4]. The well-being of people living in densely-populated areas is much lower [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence shows that urbanization decreases perceived well-being [3] and happiness [4]. The well-being of people living in densely-populated areas is much lower [3,5,6]. These findings lead to concerns about conserving urban green spaces, quality of human life, and the maintenance of human-nature contact [1,7].…”
Section: Introductionmentioning
confidence: 99%